2008
DOI: 10.1210/jc.2007-1815
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amino-Terminal Pro C-Type Natriuretic Peptide in the Neonate: Relation to Gestational Age and Postnatal Linear Growth

Abstract: Context: C-type natriuretic peptide (CNP) plays an essential role in endochondral bone growth. Insight into CNP's paracrine actions is possible using plasma measurements of the amino-terminal pro C-type natriuretic peptide (NTproCNP). Whether correlations of NTproCNP with linear growth, as found in children and lambs, apply in neonates is unknown. Objectives:Our objective was to determine the effects of prematurity, gender, and antenatal steroids on plasma NTproCNP at birth, and serial changes in hormone conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 38 publications
6
28
0
Order By: Relevance
“…Reduced CNP concentrations are also observed in umbilical blood of human newborns whose mothers were treated with glucocorticoids within 72 h of delivery (6). These findings confirm and extend these observations in showing significant inhibition of fetal CNP secretion by small increments in fetal plasma cortisol concentrations well within the range encountered in normal pregnancy.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Reduced CNP concentrations are also observed in umbilical blood of human newborns whose mothers were treated with glucocorticoids within 72 h of delivery (6). These findings confirm and extend these observations in showing significant inhibition of fetal CNP secretion by small increments in fetal plasma cortisol concentrations well within the range encountered in normal pregnancy.…”
Section: Discussionsupporting
confidence: 82%
“…In rapidly growing lambs, catabolic interventions such as caloric restriction (9) and high doses of glucocorticoids (7), well-recognized inhibitors of linear growth, rapidly and reversibly reduce circulating forms of CNP and markers of bone formation. Similar reductions in CNP forms occur in the fetus during maternal caloric restriction (10) or glucocorticoid administration (6). However, the effect of physiological increments in fetal cortisol on CNP synthesis is unknown.…”
Section: -Type Natriuretic Peptide (Cnp) Is An Important Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong associations linking growth parameters to timematched plasma NTproCNP concentrations provide further support to the in vitro studies and indicate that CNP proteins are likely to materially contribute to sustained endochondral growth. In this context, it should be noted that this association (skeletal growth and plasma NTproCNP) has been established in lambs (using metacarpal growth (Prickett et al 2005)), human neonates (tibial growth (Prickett et al 2008)), children (height, i.e. largely vertebral and lower limb growth (Prickett et al 2005, Olney et al 2009) and now in rodents (nose-tail growth, tibial length and growth plate width).…”
Section: Discussionmentioning
confidence: 91%
“…We have found that plasma concentrations of NTproCNP are closely correlated with concurrent growth velocity throughout childhood (Olney et al 2007, Prickett et al 2008, suggesting that CNP production within growth plates or closely related tissue is age dependent and acts as a driver of linear growth after birth. However, no study has examined the peptide concentrations within tissues with potential to affect skeletal growth, or how the tissue concentrations may change or relate to plasma concentrations and the growth process itself.…”
Section: ) In Contrast Tomentioning
confidence: 91%